The role of the dentist in the management of patients with amyotrophic lateral sclerosis (ALS) - Tomàs Aliberas, Jordi (2023)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that affects the center responsible for controlling muscle movement. There is currently no known cure for ALS, however there are two medications available that help slow its progress. To improve the quality of life of patients, multidisciplinary work must be carried out, where the dentist has an essential role in the management of oral health, as well as in the treatment of craniomandibular dysfunction and orofacial pain associated with the disease. A simple and effective action protocol must be established so that caregivers or family members can help in the treatment of the craniocervical region. It is proposed to carry out an action protocol based on massages, exercises and self-care to achieve an improvement in the quality of life of patients. Especially, in reducing pain, and improving masticatory and phonatory function.